Comparative Performance Of Natural Coagulants For The Treatment Of Fish Farm Wastewater - Che Yusuf, Fakhira Huda (Universiti Sains Malaysia, 2018)
A coagulation – flocculation process using chitosan and Moringa oleifera seeds extract as natural coagulants is reported for fish farm wastewater treatment in this study. The main objective to be achieved is to determine the best coagulant for highest removal of suspended solid through the coagulation - flocculation process. Therefore, optimization treatment to serve this purpose was performed using jar tests and applying a response surface methodology (RSM) to the results. A 24 full-factorial central composite design (CCD) was chosen to explain the effect and interaction of four factors: coagulant dosage, pH, mixing time and settling time. The CCD is successfully demonstrated to efficiently determine the optimized parameters, where 84% of turbidity removal was observed for wastewater samples treated with chitosan at optimized condition of 100 mg/l coagulant dosage, pH 6, 15 minutes mixing time and 10 minutes settling time and 47% of turbidity removal at optimized condition of 400 mg/l coagulant dosage, pH 10, 15 minutes mixing time and 10 minutes settling time for M. oleifera seeds extract. The wastewater samples treated using the selected optimized condition were further analyzed on their final values of ammonia, Chemical Oxygen Demand (COD), total suspended solids (TSS),total volatile solids (TVS) and phosphate concentrations. Chitosan demonstrated a better removal efficiency than M. oleifera with 64% removal on COD, 70% on TSS, 64% on VSS and 80% removal on phosphate while M. oleifera has a slightly better performance in ammonia removal efficiency at 32%. Hence, chitosan is proven to be a better choice of coagulant than M.oleifera.